Pelatihan Manajemen Program Kesehatan Lingkungan bagi Petugas Sanitasi di Puskesmas - Azis, Eyastuti; Yermi, Yermi; Pramono, Edi; Sahabuddin, Sahabuddin; Wotok, Nobertus Wuli (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Environmental health is a crucial indicator of public health development, and the role of sanitation workers in community health centers (Puskesmas) is crucial in maintaining a healthy environment. However, environmental health program implementation remains challenging due to staff's limited understanding of program management aspects, such as planning, implementation, and evaluation. This Community Service Program (PKM) activity aims to improve the capacity of sanitation workers through environmental health program management training. This activity was held at Community Health Center X over two days, involving 20 sanitation workers from the community health center's work area. The training methods used included interactive lectures, group discussions, case studies, and program development simulations. Evaluation was conducted through pre- and post-tests, as well as assessments of program development practices. The results of the activity demonstrated significant improvements in participants' knowledge and skills, particularly in designing annual activity plans based on data and local needs. This training strengthened the capacity of sanitation workers to manage environmental health programs systematically, participatory, and sustainably. It is hoped that this activity will serve as a training model that can be replicated in other community health centers to improve the quality of environmental health services.